1998
DOI: 10.1159/000028691
|View full text |Cite
|
Sign up to set email alerts
|

Massive Posterior Fossa Tuberculous Abscess Developing in a Young Child Treated for Miliary Tuberculosis

Abstract: A 21-month-old infant presented with acute obstructive hydrocephalus due to a large tuberculous abscess in the posterior fossa 3 months after starting treatment for miliary tuberculosis. Insertion of a ventriculo-peritoneal shunt resulted in some clinical improvement but subsequent neurological deterioration occurred due to massive enlargement of the tuberculous abscess despite apparently adequate antituberculosis therapy. Repeated drainage procedures of the abscess eventually resulted in resolution and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
(21 reference statements)
0
15
0
Order By: Relevance
“…Many of the studies documenting a satisfactory clinical response to an INH dose of 5 mg/kg emanate from populations with a predominance of homozygous slow acetylators; the relative therapeutic disadvantage of the heterozygote fast acetylator will also be concealed by the synergistic potential of a multidrug regimen. Under adverse circumstances, however, such as failure of full compliance, compromised absorption of INH itself, or its companion drugs, in particular rifampicin, 32 or the sequestration of organisms in poorly perfused lesions, [33][34][35] this relative disadvantage may be exposed. In the light of our findings, and in agreement with the recommendations of the American Academy of Pediatrics, we suggest that young children less than 5 years of age should receive an INH dose of at least 10 mg/kg to ensure that the faster acetylators of INH are exposed to adequate serum concentrations of INH.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the studies documenting a satisfactory clinical response to an INH dose of 5 mg/kg emanate from populations with a predominance of homozygous slow acetylators; the relative therapeutic disadvantage of the heterozygote fast acetylator will also be concealed by the synergistic potential of a multidrug regimen. Under adverse circumstances, however, such as failure of full compliance, compromised absorption of INH itself, or its companion drugs, in particular rifampicin, 32 or the sequestration of organisms in poorly perfused lesions, [33][34][35] this relative disadvantage may be exposed. In the light of our findings, and in agreement with the recommendations of the American Academy of Pediatrics, we suggest that young children less than 5 years of age should receive an INH dose of at least 10 mg/kg to ensure that the faster acetylators of INH are exposed to adequate serum concentrations of INH.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, our patient did not present atypical clinical or electrophysiological findings, despite a thorough examination. Symptoms such as facial and proximal limb weakness have been reported in different OPMD populations.…”
Section: Discussionmentioning
confidence: 49%
“…This mutation is unique but equivalent to (GCG) 9 (GCA) 3 (GCG) at the protein level, resulting in an (Ala) 13 tract. 3,11 Uyama et al confirmed that the intranuclear filamentous inclusions did indeed contain mutated PABPN1 protein. 9,10 In a recent study, Robinson et al found 13 different types of expansion mutation, six of which contained GCA and GCG, and almost all of which were consistent with a mutational mechanism of unequal recombination.…”
Section: Discussionmentioning
confidence: 98%
“…3 4-year-old girl treated for miliary tuberculosis. 4 Primary cerebellar involvement, as in our case, is even rarer and the mortality rate is high 5 (10-15%) as the CSF pathway may be suddenly totally occluded, leading to acute hydrocephalus, coma and death. Prakash et al 6 reported three cases of tuberculous abscesses in the brainstem and a pontine location was described by Prasad et al 7 In a clinico-pathological review of tuberculous brain abscesses by Chakraborti et al, 8 only four paediatric cases of TB cerebellar involvement were seen, three of whom had no past history of TB.…”
Section: Discussionmentioning
confidence: 55%